Manajemen Kurikulum Pendidikan Agama Islam dan Perbaikan Karakter Peserta Didik - Fitriani, Euis; Nurzaman, Nurzaman (Jurnal Penelitian Pendidikan Islam, 2017)
This article discusses the results of research on Islamic education curriculum management in Elementary School. The results showed that: (1) Planning of Islamic education curriculum using of KTSP curriculum. The design of Islamic education curriculum emphasizes learning experience. (2) The organizing of Islamic Religious Education curriculum is grouped into several fields: theology, morals, Qur'an and Hadith, fiqh, Islamic history, and Arabic language. (3) The implementation of PAI curriculum involves the role of principals, teachers, character based lesson plans, habituation and exemplary, as well as extracurricular activities. (4) Evaluation of learning used is the assessment process by observing student activities and assessment of the task (portfolio) and monitor the success of learning in the classroom.